The case of the phantom cat - Webb, Holly (Webb, Holly. Mysteries of Maisie Hitchins., 2015)
Alice's father invites twelve-year-old Maisie and her dog Eddie to join Alice on a trip to the country, but the manor her father has rented seems to be haunted, terrifying Alice and putting Maisie's detecting skills to the test. Includes quizzes, activities, and more.